(untitled) (Journal of Medicine, 2012)
Background: Haemoglobin and haematocrit estimation are the commonest methods used worldwide in Blood Banks to screen donors. In order to detect Non-anaemic iron deficient state in repeat donors, these tests are inadequate. Several studies have reported a high incidence of iron deficiency in repeat donors. Aims: The present study was undertaken to assess routine haematological parameters and body iron stores of blood donors in order to identify those who were potentially prone to develop iron deficiency anaemia. Method: Predonation haemoglobin, haemogram and serum ferritin were done in 116 male donors. These were divided into two groups on the basis of number of donations. Results: First time donors (81.07±97.12) had higher mean serum ferritin level than those in repeat donors (46.01±49.09). 10.52% of first time donors and 27.5% of repeat blood donors were found to be iron deficient as indicated by serum ferritin level <12 ng/ml. In addition a higher RBC count, reticulocyte % and lower MCV were noted in repeat donors. Conclusion: We concluded that haemoglobin estimation was not adequate to detect iron deficient non anaemic state in repeat blood donors. Serum ferritin proved to be a better investigation to detect the same and should be done in repeat donors. Iron supplementation for an adequate period post donation is recommended. DOI: http://dx.doi.org/10.3329/jom.v13i2.12754 J Medicine 2012; 13 : 174-178